Who is to judge?: the perennial debate over whether to elect or appoint America's judges - Geyh, Charles Gardner (Oxford University Press, 2019)
Introduction -- A short and pointed history of judicial selection -- The new judicial selection landscape -- The arguments -- Why everyone is wrong -- Managing the selection debate -- The future of judicial selection